Consumer Choice between Hedonic and Utilitarian Goods - Dhar, Ravi; Wertenbroch, Klaus (Journal of Marketing Research, 2000)
In this article, the authors examine how consumer choice between hedonic and utilitarian goods is influenced by the nature of the decision task. Building on research on elaboration, the authors propose that the relative salience of hedonic dimensions is greater when consumers decide which of several items to give up (forfeiture choices) than when they decide which item to acquire (acquisition choices). The resulting hypothesis that a hedonic item is relatively preferred over the same utilitarian item in forfeiture choices than in acquisition choices was supported in two choice experiments. In a subsequent experiment, these findings were extended to hypothetical choices in which the acquisition and forfeiture conditions were created by manipulating initial attribute-level reference states instead of ownership. Finally, consistent with the experimental findings, a field survey showed that, relative to market prices, owners of relatively hedonic cars value their vehicles more than do owners of relatively utilitarian cars. The authors discuss theoretical implications of these reference-dependent preference asymmetries and explore consequences for marketing managers and other decision makers.